Respon Pertumbuhan Protocorm Like Bodies (PLB) Anggrek Tebu (Grammatophyllum scriptum Blume) terhadap Modifikasi Media Murashige and Skoog (MS) secara In Vitro - Ratna Kusuma; Samsurianto Samsurianto; Wafif Azizah; Ervinda Yuliatin (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Anggrek Tebu (Grammatophyllum scriptum) propagation can be improved optimally by adding plant growth regulators such as BAP and NAA through in vitro technique. Murashige and Skoog (MS) medium is an essential medium for plant tissue growth that needs another complex mineral and vitamin to develop the protocorm-like bodies (PBL) of Anggrek Tebu. Hence, this study aimed to gain the appropriate composition of modified MS by adding BAP and various coconut water concentrations and to evaluate their effect on PBL of Anggrek Tebu growth (budding time, number of buds, and leaves). The research was conducted using a completely randomized design with two factorials such as modified MS medium (MS (M1), ½ MS (M2), and ¼ MS (M3))and coconut water concentration (0 ml/L (C0), 100 ml/L (C1), 200 ml /L (C2), and 300 ml/L (C3)) with triplication. The result showed that the fastest budding time was remarkable growth from M2C1 offered the bud at three weeks after planting (WAP). In the number of budding, M3C2 showed excellent results and significantly increased the budding growth at 8.33 ± 0.88 in 10 WAP. Meanwhile, the highest leave number was M2C1 at 23.00 ± 3.60, followed by M2C2 and M3C2, respectively, at 20.67 ± 1.45 and 20.67 ± 1.33. This result indicated that modifying MS medium composition by adding the coconut water could assist the PBL of Anggrek Tebu growth in a specific concentration.